THE ROLE OF PHOTOJOURNALISTS IN ONLINE MEDIA PHOTOJOURNALISM DETIK.COM - Muzakki, Naufal; Irawan, Rahmat Edi (Transpublika Publisher, 2024)
Journalism is one of the most dynamic professions. Likewise, photojournalists are always required to keep abreast of the latest developments and, as much as possible, share the latest stories of an event. In this digital era, the author sees that increasingly online media currently put forward photojournalism. Photojournalism is used in online media to put forward visual messages as reinforcement of messages from events or events to the public. One of them is Detik.com. Detik.com is a connected media content provider. This research uses qualitative research with a descriptive research type. From the results of research, discussion, and analysis that have been collected, the authors conclude that photojournalists, in carrying out the process of taking journalistic photos, must meet the main components in the news, namely 5W + 1H, by existing and applicable journalistic rules and ethics and use photographic techniques following events or events in the field. In taking photos, photojournalists must follow the guidelines from pre-production to post-production under directions from the leadership until the editorial team approves the photo, visual, or image until the news is uploaded. The role of photojournalists supports the report uploaded by Detik.com. The gatekeeping scheme played by photojournalists is also crucial at three stages, namely the individual level, media routines, and organization, so the news uploaded by Detik.com has high credibility.